Accuracy of Fibula Reconstruction Using Patient‐Specific Cad/Cam Plates: A Multicenter Study on 47 Patients. (16th January 2021) - Zavattero, Emanuele; Bolzoni, Alessandro; Dell'Aversana, Giovanni; Santagata, Mario; Massarelli, Olindo; Ferri, Andrea; Della Monaca, Marco; Copelli, Chiara; Gessaroli, Manlio; Valsecchi, Stefano; Borbon, Claudia; Beltramini, Giada Anna; et al.
Abstract : Objectives: This prospective study evaluated the accuracy of mandibular reconstruction using free fibular flaps (by comparing virtual plans to the three‐dimensional postoperative results), and the extent of bone‐to‐bone contact after computer‐assisted surgery. Methods: We included 65 patients who underwent partial‐continuity mandibular resections from February 2013 to January 2017, and evaluated virtual planning, surgical techniques, and accuracy. Results: Forty‐seven patients were analysed. A total of 112 fibular segments received 54 implants. We measured 227 distances between landmarks to assess the accuracy of reconstruction. Postoperative reconstruction accuracy ranged from 0.5 to 3 mm. Conclusion: Virtual surgical planning very accurately translated simulation into reality, particularly in patients requiring large, complex mandibular reconstructions using multiple fibular segments. Level of evidence: 4 Laryngoscope, 131:E2169–E2175, 2021